Third-generation three-dimensional display system for laparoscopic radical nephrectomy reduced surgical complications compared to a two-dimensional display system. (September 2022) - Fujishima, Yosuke; Takata, Ryo; Tsuyukubo, Takashi; Kanzaki, Seiko; Isurugi, Kazumasa; Kato, Yoichiro; Kanehira, Mitsugu; Obara, Wataru
Objective: Compared with two-dimensional (2D) laparoscope systems, conventional three-dimensional (3D) systems provide a superior understanding of depth. However, they are operator limited due to difficulties with resolution and illumination. A novel third-generation (3G) 3D system may resolve these problems. We prospectively compared the operative performance and perioperative safety results of 2D and 3G 3D systems in laparoscopic radical nephrectomy (LRN). Patients and methods: A single experienced surgeon performed 3G 3D LRN for 19 patients and 2D LRN for 16 patients. After the insertion of the access ports, the execution times of each step in the surgical procedure in the two groups were measured and compared, along with the perioperative complications. Results: Patients in the 3D group were associated with fewer complications than those in the 2D group. In particular, no peritoneal injury was observed in the 3D group (0% vs. 25%, p =0.04). Logistic regression analysis showed no significant differences between the times of each surgical step and the amount of bleeding. Conclusions: The 3G 3D laparoscope system provided a detailed anatomical view for the operator during LRN and may reduce laparoscopic complications. Level of evidence: III.